Предмет: Алгебра,
автор: алах19
2x-3 x+1
____ + ____= 2
x+1 2x-3
используй метод замены переменной
Ответы
Автор ответа:
0
(2x-3)/(x+1)+(x+1)/(2x-3)=2 ОДЗ: 2x-3≠0 2x≠3 x≠1,5 x+1≠0 x≠-1
Пусть: 2x-3=t x+1=v ⇒
t/v+v/t=2 |×t*v
t²+v²=2*t*v
t²-2*t*v+v²=0
(t-v)²=0
t-v=0
2x-3-(x+1)=0
2x-3-x-1=0
x-4=0
x=4.
Ответ: x=4.
Пусть: 2x-3=t x+1=v ⇒
t/v+v/t=2 |×t*v
t²+v²=2*t*v
t²-2*t*v+v²=0
(t-v)²=0
t-v=0
2x-3-(x+1)=0
2x-3-x-1=0
x-4=0
x=4.
Ответ: x=4.
Похожие вопросы
Предмет: География,
автор: shodiiarkarimov
Предмет: Русский язык,
автор: ajgerimkemelbaj
Предмет: Алгебра,
автор: cehnoanzela
Предмет: Алгебра,
автор: marina442